Global expansion and redistribution of Aedes-borne virus transmission risk with climate change - Ryan, Sadie J.; Carlson, Colin J.; Mordecai, Erin A.; Johnson, Leah R. (PLOS Neglected Tropical Diseases, 2019)
Author summary The established scientific consensus indicates that climate change will severely exacerbate the risk and burden of Aedes-transmitted viruses, including dengue, chikungunya, Zika, and other significant threats to global health security. Here, we show more subtle impacts of climate change on transmission, caused primarily by differences between the more heat-tolerant Aedes aegypti and the more heat-limited Ae. albopictus. Within the next century, nearly a billion people could face their first exposure to viral transmission from either mosquito in the worst-case scenario, mainly in Europe and high-elevation tropical and subtropical regions. However, while year-round transmission potential from Ae. aegypti is likely to expand (particularly in south Asia and sub-Saharan Africa), Ae. albopictus transmission potential is likely to decline substantially in the tropics, marking a global shift towards seasonal risk as the tropics eventually become too hot for transmission by Ae. albopictus. Complete mitigation of climate change to a pre-industrial baseline may protect almost a billion people from arbovirus range expansions; however, middle-of-the-road mitigation could produce the greatest expansion in the potential for viral transmission by Ae. albopictus. In any scenario, mitigating climate change would shift the projected burden of both dengue and chikungunya (and potentially other Aedes transmitted viruses) from higher-income regions back onto the tropics, where transmission might otherwise begin to decline due to rising temperatures.